An in-depth assessment of pastoral policy landscape in Kenya - S. Wagura Ndiritu; Ann Mukami Gachuki Waimiri; Arnold Muthanga; Shruthi Baskaran-Makanju (Pastoralism)
The policy landscape explores the policy formulation processes, the policies, and the stakeholders involved in improving governance, implementation of policies, and government commitment in a democratic country. It emphasizes the human development approach that is within the Pastoralism Framework of the African Union (AU), recognizing the link between economic growth and human development through deliberate policies at various levels. The integrated strategies in Kenya’s pastoral policy landscape aim to evaluate progress against the objectives of national development projects and how those objectives are integrated into County-Integrated Development Plans (CIDPs) and outcomes based on Metland’s Ambiguity-Conflict Model. This landscape seeks to frame and advance the changing dynamic of how the current policies and strategies align with the realities of the pastoral sector with an emphasis on livestock production and marketing but recognizing pastoralists are involved in other economic activities such as opportunistic irrigation, fishing, beekeeping, quarry mining, firewood, liquor production, and casual labor. Doing so is to support the alleviation of persistent multidimensional poverty in those regions and improve communication (at the intra-and inter-governmental levels), coordination, and flow of county-level heterogeneous information in support of a centralized policymaking process. It also identifies ways to prioritize pastoral livestock marketing, integrate pastoral issues in decision-making, empower women, and adopt climate adaptation for holistic pastoral transformation.